Intussusception due to non Hodgkin’s lymphoma; different experiences in two children: two case reports - Shakya, Vikal Chandra (Cases Network Ltd, 2009)
In children, non-Hodgkin’s lymphoma has been found to be the lead point in intussusception involving the terminal ileum. We present here two cases of ileal primary non-Hodgkin’s lymphoma which presented as intussusception, highlighting the differing presentations of these children and their outcome, with a brief review of the literature.